A Pilot Study For Evaluating Egyptian Health Websites: Technical And Ethical Perspectives (Bangladesh Journal of Bioethics, 2012)
Background: The growing popularity of the Internet has made it easier and faster to find health information. Much of this information is valuable; however, the Internet also allows rapid and widespread distribution of false and misleading information. Aim of the work: To evaluate some of the Egyptian health websites from the Technical and Ethical perspectives and to compare the reliability of the different types of Egyptian health websites. Materials and Methods: This is a descriptive study. Search engines (eg. Google.com and Yahoo.com) were thoroughly searched for Egyptian health websites. Some of these websites were not accessible. Out of thirty two health websites, thirteen internet health websites were randomly selected and evaluated twice in this study. They were classified into 4 categories, official, professional, educational and private. The tool used in this study was a questionnaire developed by the research team depending on EHealth code of ethics, 2000 and international technical guidelines. The questionnaire consists of two main categories (technical and ethical). The technical evaluation includes (authority, objectivity, coverage, currency, design, privacy and security). The ethical evaluation includes (quality of information, informed consent and professionalism). A score for the questionnaire was developed by the research team to assess the websites. All statistical analyses were performed using the Statistical Package for Social Science (SPSS) version 11.0. Comparisons between ethical and technical categories were done using the student’s t-test and ANOVA test for continuous variables and Pearson’s Chi square test for categorical variables. Results: On evaluating the quality of information of the health websites, it is noticed that in 92.3% of the sample, medical care is provided by professionals and their information based on scientific studies. Around forty six percent (46.2%) of the health websites do not mention the date of publication, date of recent update and the source of the information. Concerning the professionalism, 100% of the sample obeys laws and regulation in identifying themselves and mentioning the limitation of online consultation. 76.95% of the sample states clearly the purpose of the health website. Only 38.5% of them were recently updated. Privacy policy evaluation shows that 33.3% mentions if the system prevents unauthorized access to personal data while only 16.7% states how the user's personal data is stored and for how long. There is a statistically a significant change (p